Impact of Rural fixed assets investment on Agricultural Economic Growth and Farmers’ Income: Evidence from agriculture in China - Wang, Yun; Ban, Ge (Migration Letters, 2024)
As one of the "troikas" to promote agricultural economic growth, rural fixed assets investment plays an important role in increasing farmers’ income and promoting rural economic development. This article selects agricultural data from various provinces in China during the 13th Five Year Plan period from 2016 to 2020 as the research object. Construct an agricultural economic performance evaluation system and calculate the comprehensive performance score through factor analysis. Then, on this basis, the panel is established to verify the impact of rural fixed assets investment on agricultural economic performance and farmers’ income through multiple regression. The results show the use of pesticides and regional economic differences hurt the improvement of agricultural economic benefits and the increase of farmers’ income. Therefore, we should strengthen the overall management and structural optimization of rural fixed assets investment, accelerate rural economic development, and improve the income level of farmers.